1993
DOI: 10.1288/00005537-199303000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism induced by hypothyroidism

Abstract: The coexistence of hyperparathyroidism and thyroid tumors and/or chronic thyroiditis has raised the possibility of an etiologic relationship. The present study was designed to test the hypothesis that the chronic elevation of thyroid-stimulating hormone (TSH) is related to the development of hyperparathyroidism. Three groups of 24 rats each were treated for 12 weeks as follows: group 1 received propylthiouracil (PTU) in their deionized water; group 2 received PTU and thyroid hormone to suppress TSH and to serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In our previous study, limited to 12 weeks of observation, we demonstrated parathyroid hyperplasia in 95% of the animals treated with PTU and a 30% increase in the circulating PTH levels 32 . These findings lent support to the hypothesis that chronic hypothyroidism may lead to the development of hyperparathyroidism.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our previous study, limited to 12 weeks of observation, we demonstrated parathyroid hyperplasia in 95% of the animals treated with PTU and a 30% increase in the circulating PTH levels 32 . These findings lent support to the hypothesis that chronic hypothyroidism may lead to the development of hyperparathyroidism.…”
Section: Discussionsupporting
confidence: 74%
“…The hyperplastic changes i n the parathyroids of the PTUtreated rats did not appear to be due only to the direct effect of PTU on parathyroid tissue, because these changes were not seen in the euthyroid animals treated with both PTU and thyroxine. 32 These preliminary results led to this long-term study to determine whether a full hyperparathyroid state could be produced in chronically hypothyroid rats.…”
Section: Introductionmentioning
confidence: 99%
“…8 This has been demonstrated in the rat model, with experimental elevation of thyroid-stimulating hormone (TSH) leading to significant concurrent elevations in PTH and subsequent development of parathyroid adenomas. 9,10 Alternatively, hypothyroid dogs may have smaller thyroid gland size, possibly leading to more mobility of the parathyroid nodule and subsequent difficulty with correct needle placement during parathyroid ablation. However, the effect of thyroid size was not seen when considering all dogs that underwent parathyroid ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in rats using propylthiouracil to stimulate TSH showed that chronic TSH stimulation led to parathyroid hyperplasia and an increase in circulating PTH. It is postulated that prolonged TSH stimulation and may lead to hyperparathyroidism in animal models 36 37…”
Section: Discussionmentioning
confidence: 99%